Incubator with food object detection based automatic heating process using internet of things technology - Heru Supriyono; Agus Supardi; Pramudya Kurnia; Mohammad Dwiki Aji Nugroho; Muhammad Satria Ananta; Helmi Hidayatullah (Bulletin of Electrical Engineering and Informatics, 2026)
Conventional incubators for heating food generally can be operated manually by both its temperature level and heating duration. This condition provides risk that the food will be heated inappropriately both at its temperature level and heating duration which in turn can decrease food quality. The objective of this article is to develop an incubator for heating food which is equipped with a food object detection based automatic heating process and using internet of things (IoT) technology for distance monitoring and control, which detects the type of food and heating it automatically at both temperature level and duration. The incubator was developed using components available in the market including GY-906-DCI sensor, OV5647 camera, Raspberry Pi 4, NodeMCU microcontroller, and Telegram bot. Testing results showed that the developed incubator system was able to detect food types in real-time, as well as automatically set temperature and incubation time parameters based on it. It was able to maintain a stable incubation temperature, with an average error of 2.74% and a temperature deviation of 1.23 °C. The developed incubator potentially improves safety and user convenience where the food is heated properly both at its temperature level and heating duration.